2009
DOI: 10.1007/s00270-009-9755-8
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience with the Amplatzer Vascular Plug II for Occlusive Purposes in Arteriovenous Hemodialysis Access

Abstract: The Amplatzer Vascular Plug Type II (AVP II) has proven effective in the therapeutic embolization of various vascular lesions. It benefits from very rapid occlusion of the target lesion and can be deployed, retrieved, and redeployed if required. There is no literature available on use of the AVP II in the maintenance, closure, and management of complicated arteriovenous access in hemodialysis patients. In this series, we present our clinical experience with the use of the AVP II for embolization of problematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…Today, AVP has a wide use for extracardiac procedures such as arterial and venous embolization. Single cases of AVP use in embolization AVFs have also been reported [5], [8], [9]. To our knowledge only 3 cases of AVP use as a coil constrainer were described [5], [8], [9], and surely no cases of giant aneurysm.…”
Section: Discussionmentioning
confidence: 89%
“…Today, AVP has a wide use for extracardiac procedures such as arterial and venous embolization. Single cases of AVP use in embolization AVFs have also been reported [5], [8], [9]. To our knowledge only 3 cases of AVP use as a coil constrainer were described [5], [8], [9], and surely no cases of giant aneurysm.…”
Section: Discussionmentioning
confidence: 89%
“…Powell et al [ 8 ] reported on 7 patients with complicated HD access who were treated with AVP. Their complex venous anatomy, wound healing, and severe local conditions made surgical ligation challenging.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of literature on the application of the same AVP type II used in our case for various conditions: the occlusion of a spontaneous mesocaval shunt (15), to treat a type II endoleak after endovascular thoraco-abdominal aortic aneurysm repair (16, 17), and to occlude an arteriovenous hemodialysis access (18). Generally, the AVP should be oversized by approximately 20% of the vessel diameter.…”
Section: Discussionmentioning
confidence: 99%